Archetypal Images of Causality in English, Dutch, Spanish, Ukrainian, and Russian Sayings: A Comparative Study - Lemish, Nataliya; Kaliberda, Oksana; Aleksieieva, Olha; Tsymbalysta, Oksana (Journal of History Culture and Art Research, 2019)
The paper deals with the comparative study of archetypal images of causality in English, Dutch, Spanish, Ukrainian, and Russian sayings. The object of the research is the category of causality represented in the human mind as a sentential (syntactic) concept with ten causal dominants (cause, reason, condition, concession, purpose, effect, conclusion, result, consequence, means). The subject matter of this paper covers etymons and archetypal images of the causal dominants in five related languages. The objective to compare archetypal images of causality reconstructed on the basis of the English, Dutch, Spanish, Ukrainian, and Russian sayings can be achieved through solving such tasks as follows: specifying the source for archetypal images reconstruction; identifying the etymons for the causal dominants in studied languages; elaborating the archetypal images of causality based on the sayings from near-related (English and Dutch, Ukrainian and Russian), and far-related (English and Spanish, English and Ukrainian, English and Russian) languages. The major linguistic method employed to achieve the objective is a comparative and historical one, including the results of etymological analysis presented in the dictionaries. Relevant methods also include structural (immediate constituents and componential analysis) and contextual-interpretative ones. The present actual language data for the research were taken from different etymological dictionaries and sayings from the languages under study. The obtained results confirm that the reconstruction of etymons of causal dominants, as well as of the archetypal images of causality in different languages enables gaining important information about the peculiarities of causal thinking and psychology of various ethnic groups. In addition, the ability of the archetypes to be modified by penetration into the consciousness of people and filling the empty signs with the data of conscious experience is revealed.